Solid State Transformer Controls for Mitigation of E3a High-Altitude Electromagnetic Pulse Insults - Connor A. Lehman; Rush D. Robinett; Wayne W. Weaver; David G. Wilson (Energies)
This paper explores the use of a solid state transformer (SST) to mitigate the <semantics>E3A</semantics> component of a high-altitude electromagnetic pulse (HEMP) insult using external energy storage optimal control techniques. In lieu of conventional passive blocking devices or feedback-controlled energy storage devices, a novel implementation of Hamiltonian error tracking is utilized to develop a feedback control law for the variable converter ratio in an SST. The findings of the simulations performed in this paper suggest that additional energy storage is not necessary to protect an individual load from a HEMP insult. The simulations performed examine the response of a single-phase SST connected to a single voltage source on a long transmission line on the one side and a single linear resistor on the other. The control law is specifically developed for the late-time, low-frequency portion of a HEMP insult, namely the <semantics>E3A</semantics> components. The Hamiltonian error-based converter ratio control law is compared with nonlinear optimal feedforward controls to show that the HSSPFC is an external energy storage optimal controller.